1993
DOI: 10.1111/j.1398-9995.1993.tb01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of specific IgE antibodies in allergic contact sensitivity to formaldehyde

Abstract: Immunologic reactions are customarily divided into two broad categories, cell-mediated and antibody-mediated. An interplay between these two pathogenetic principles is indicated by reactions such as cutaneous basophil hypersensitivity, late-phase reaction, and cutaneous lesions indistinguishable from regular allergic contact dermatitis lesions after sensitization with IgE antibodies against certain haptens. In the present study, 23 patients with a history of a positive epicutaneous test to formaldehyde partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
(11 reference statements)
0
11
0
Order By: Relevance
“…An important consideration is the fact that in the experiments described here, a differential quality of immune response is induced following cutaneous exposure to formaldehyde or glutaraldehyde. As such, the preferential activation of type 1, IFN‐γ‐secreting, LNCs and the failure to elicit increases in the total serum concentration of IgE following topical application of formaldehyde to mice [ 38, 41], are consistent with the inability to detect specific IgE antibody in patients with formaldehyde‐induced atopic dermatitis [ 45]. There is good reason to suppose that, due to the systemic nature of the immune system, topical exposure to chemical respiratory allergens can result in effective sensitization of the respiratory tract.…”
Section: Discussionmentioning
confidence: 95%
“…An important consideration is the fact that in the experiments described here, a differential quality of immune response is induced following cutaneous exposure to formaldehyde or glutaraldehyde. As such, the preferential activation of type 1, IFN‐γ‐secreting, LNCs and the failure to elicit increases in the total serum concentration of IgE following topical application of formaldehyde to mice [ 38, 41], are consistent with the inability to detect specific IgE antibody in patients with formaldehyde‐induced atopic dermatitis [ 45]. There is good reason to suppose that, due to the systemic nature of the immune system, topical exposure to chemical respiratory allergens can result in effective sensitization of the respiratory tract.…”
Section: Discussionmentioning
confidence: 95%
“…Several epidemiological studies have demonstrated that FA exposure can induce or exacerbate asthma [34][37]. Unlike typical allergens, FA-specific IgE is rarely detected [38], [39], which suggests that FA may be involved in asthma via a non-IgE-mediated mechanism. Two possible pathways for FA-induced asthma have been proposed: the irritant effect and the adjuvant effect [40].…”
Section: Introductionmentioning
confidence: 99%
“…Dykewicz et al 13) suggested that clinical IgE-mediated allergy to gaseous FA does not exist, or if it does, is extremely rare. Also, a study by Liden et al 14) did not support the hypothesis that specific IgE antibodies are active in the pathogenesis of contact sensitivity to FA either in atopic or nonatopic patients. Thus IgE-mediated sensitization to FA is controversial, as mentioned above.…”
Section: Introductionmentioning
confidence: 79%